Spontaneous massive Streptococcus constellatus empyema thoracis in a healthy individual: a case report - A., Zulkifli; M. M., Muhammad Nasri; W. M., Rosmaiza; O., Noorkardiffa Syawalina; M. N., Nurul Huda; A., Razif (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2022)
Empyema thoracis is a well-known condition that is characterised by a collection of pus in the pleural space and has historically been related to high mortality rate. The cause of high mortality rate is unknown, but it may have higer risk in pneumonia cases or immunocompromised patients. This case study presented a 50-year-old man with no chronic co-morbidities, admitted with the diagnosis of sepsis secondary to community-acquired pneumonia, which was covered with ceftriaxone. Subsequently, he developed massive spontaneous right lung empyema, necessitating an urgent thoracotomy and comprehensive right decortication. Broad-spectrum antibiotics, meropenem, was then given to him. Streptococcus constellatus was discovered in the pleural fluid’s culture and sensitivity test. On his tenth day of stay, the patient had a right thoracotomy and decortication. The patient was extubated on day two post-operative and recovered on subsequent days. He was then discharged at 30 days post-operatively. We reported a case of adult spontaneous empyema thoracis from a patient with few risk factors: he was not immunocompromised, had no chronic illnesses and had no interaction with tuberculosis patients.